A review on the management and conservation of forest biodiversity in the context of SFM of the tropical rain forest - Borhan, M. (Forestry Department Peninsular Malaysia, 2015)
Ever since the advent of civilization, human population has continued to increase geometrically in the face of increasingly limited natural resources. The speed of change, particularly over the past century, present governments with problems of unusual complexity in planning the best allocation and management of landand these problems are further complicated by growing shortages of raw materials and rising cost of production throughout the world (Poore, 1976). Uncontrolled and uncoordinated exploitation have given rise to a critical situation termed as "Tragedy of the Commons" whereby the continued exploitation of natural resouces has led to their depletion along with the degradation of the environment (Senge, 1990)Ingham, 2005). Examples of the latter include the present state of the world`s fisheries, the drop in farmlands productivity in developing countries, acid rains, green-house effect (i.e global warming), climate change and the largerly unsustainable management of the Tropical Rain Forest (TRF) causing genetic depletion and reduction in species biodiversity. Protocols and global strategies developed during the Earth Summit in Rio de Janeiro in 1992 were meant to deal with these issues, along with other worsening phenomena such as global warming, climate change and sustainable development particularly in developing countries. In this paper, the situations with regard to the issues of the sustainable management of the TRF biodiversity and conservation are reviewed with special attention being paid to the situation in Southeast Asia in general and Peninsular Malaysia in particular-past experiences of the different countries, problems and constraints faced as well as strategies for the future-all in the context of the increasingly globalised approach in socio-politico and environmental management.